Surface EEG Evidence for Cerebellar Control of Distal Upper Limbs in Humans - Anna Latorre; Kais Humaidan; Mauro Sanna; Maria Lucrezia Lavena; Sara Pittalis; Clio Raimondi; Elias Paolo Casula; Lorenzo Rocchi (Brain Sciences)
Background/Objectives: The cerebellum plays a crucial role in motor control, but its direct electrophysiological investigation in humans is challenging. Electrocerebellograms (ECeGs), recorded via surface electrodes below the inion, have been proposed as a non-invasive method to assess cerebellar activity. However, its interpretation is complicated by potential interference from occipital alpha rhythms and neck muscle signals. This study aimed to investigate whether ECeG signals genuinely reflect cerebellar involvement during upper limb movement and to explore possible confounding influences. Methods: We recorded electroencephalograms (EEGs) from occipital (Oz) and cerebellar electrodes (Cb1 and Cb2), alongside EMGs from forearm muscles in healthy individuals performing sinusoidal (~1 Hz) and tremor-like (~4 Hz) wrist movements. To assess occipital contamination, recordings were obtained under both eyes-open and eyes-closed conditions. Results: Occipital alpha power was present in Cb1 and Cb2 but was less affected by eye-opening than at Oz, suggesting a partially distinct neural source. During the tremor condition, movement-frequency power increased at Cb2 and C3 (corresponding to the ipsilateral cerebellar hemisphere and contralateral motor cortex), indicating authentic cerebellar activity. No significant movement-related EEG changes were observed during sinusoidal movements, likely due to weaker neuronal synchronization. Conclusions: These findings suggest that ECeGs can detect cerebellar signals linked to movement, especially during faster and rhythmic motions, and are only moderately affected by occipital contamination. This supports the feasibility of non-invasive cerebellar electrophysiology and underscores the need for further methodological refinement to enhance signal specificity.